Handbook of research on management techniques and sustainability strategies for handling disruptive situations in corporate settings - Pérez Uribe, Rafael Ignacio (Business Science Reference, 2022)
"This book aims to identify what makes companies that work in organizational chaos and in a chaotic economic environment perform better than companies that are well organized while also presenting management techniques and sustainability strategies for handling disruptive situations in corporate settings"--